2021
DOI: 10.4085/1062-6050-164-20
|View full text |Cite
|
Sign up to set email alerts
|

Foot Posture and Plantar Loading With Ankle Bracing

Abstract: Context Arch height is one important aspect of foot posture. An estimated 20% of the population has pes planus and 20% has pes cavus. These abnormal foot postures can alter lower extremity kinematics and plantar loading and contribute to injury risk. Ankle bracing is commonly used in sport to prevent these injuries, but no researchers have examined the effects of ankle bracing on plantar loading. Objective To evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The mean force was normalized to body weight (BW) for each subject. The contact area was normalized to the total contact area of the insole and therefore is reported in units of normalized insole contact area (NICA) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mean force was normalized to body weight (BW) for each subject. The contact area was normalized to the total contact area of the insole and therefore is reported in units of normalized insole contact area (NICA) [21].…”
Section: Discussionmentioning
confidence: 99%
“…After the selection and screening of 499 titles and abstracts, 67 duplicated studies were removed, and a total of 432 studies were taken into account during the screening procedure. Then, 12 trials mentioned intervention with assistive devices for pes cavus in the abstract, of which 2 were excluded as retrospective analyses of previous trials, 5 were excluded as ineligible interventions, 1 was excluded as ineligible comparators, 1 was excluded as having no raw data, and 3 were included in the final analysis [13,21,38]. The flow diagram is presented in Figure 1.…”
Section: Search Selection and Screening Of Studiesmentioning
confidence: 99%
“…Additionally, considering the chronic ankle instability induced by pes cavus, ankle braces may also serve as a non-surgical intervention to prevent and alleviate pes cavus symptoms, redistributing the load on the sole. However, the mechanism of its effect on preventing and alleviating pes cavus needs further investigation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal postures may also have the opposite effects of causing pain and increasing the risk of sports injuries. For example, flat feet and high arches can alter the limb line and increase the risks ( 16 ). A cross-sectional study found that people who use computers on a daily basis reported more shoulder and neck pain and numbness than those who do not use computers ( 17 ).…”
Section: Introductionmentioning
confidence: 99%